Civil engineering procedure (ICE Publishing, 2016)
Civil Engineering Procedure, Seventh edition is the essential reference for student and graduate engineers. It offers comprehensive, expert guidance on every key stage of an engineering project, from conception and development through to completion and handover-- Publisher.
Keywords: Engineering -- Management.; elektronické knihy; electronic books